MODELING CYCLES IN ECONOMETRIC MODELS - Anatoly B. Yusov; Antonina A. Kasatkina (Статистика и экономика, 2016)
The paper describes the author’s algorithm for ﬁnding the cyclical components.All time series consist of 4 components,namely trend, seasonal, cyclic and residual component. In the domestic literaturedescribes only to ﬁnd the trend, seasonal and residual components. And findingcyclic components is similar to ﬁndingseasonal. The author believes that the algorithm for ﬁnding the seasonal andcyclical cannot be the same.